Effect of heavy strength training on muscle thickness, strength, jump performance, and endurance performance in well-trained Nordic Combined athletes - Rønnestad, B. R.; Kojedal, Ø.; Losnegard, T.; Kvamme, B.; Raastad, T. (European Journal of Applied Physiology, 2012)
The purpose of the present study was to investigate the effect of supplemental heavy strength training on muscle thickness and determinants of performance in well-trained Nordic Combined athletes. Seventeen well-trained Nordic Combined athletes were assigned to either usual training supplemented with heavy strength training (STR; n = 8) or to usual training without heavy strength training (CON; n = 9). The strength training performed by STR consisted of one lower-body exercise and two upper-body exercises [3-5 repetition maximum (RM) sets of 3-8 repetitions], which were performed twice a week for 12 weeks. Architectural changes in m. vastus lateralis, 1RM in squat and seated pull-down, squat jump (SJ) height, maximal oxygen consumption (VO2max), work economy during submaximal treadmill skate rollerskiing, and performance in a 7.5-km rollerski time trial were measured before and after the intervention. STR increased 1RM in squat and seated pull-down, muscle thickness, and SJ performance more than CON (p < 0.05). There was no difference between groups in change in work economy. The two groups showed no changes in total body mass, VO2max, or time-trial performance. In conclusion, 12 weeks of supplemental strength training improved determinants of performance in Nordic Combined by improving the athletes` strength and vertical jump ability without increasing total body mass or compromising the development of VO2max.